Assistance in using Sipikan Website to increase sales of fishermen in Seri Village Sub-District Nusaniwe - Paskanova Christi Gainau; Trisye Natalia Kilay; Angela Ruban; George Adolfo Pattiasina; Natalia Evernande Gomies (University of Merdeka Malang, 2024)
The viability of the fishing industry as a business depends on the sea's condition, as operating patterns rely on environmental factors affecting daily costs. Operational expenses tend to rise without proportional increases in turnover. One solution for fishermen is maximizing fish sales online via a website, reducing transportation costs and enabling better pricing. This service program aims to empower fishermen through digital tools to enhance efficiency and market access. Using Participatory Action Research (PAR), the program includes socialization, training, mentoring, and evaluation. Outcomes showed participants enthusiastically welcomed the Sipikan website. Training improved their comprehension and proficiency, while post-tests indicated increased confidence, initiative, motivation, leadership, and risk-taking. This program demonstrates digital platforms' potential to enhance the sustainability and profitability of small-scale fishing enterprises. Ongoing support is essential to ensure fishermen independently address challenges using the website. Additionally, government policies should encourage MSMEs, especially micro-scale associations, to adopt digital platforms for further growth.